A joke for you, a status-boost for men: Men’s tendency to tell affiliative jokes is related to their self-promotion style - Jach, Łukasz; Pietrzak, Gabriela (Studia Psychologica: Theoria et praxis, 2022)
A sense of humor is a desirable characteristic in both romantic and platonic relationships, and people communicate their sense of humor by telling jokes. However, there are sex differences in joking, so men tell jokes more often than women. Men’s benefits from joking correspond with such fundamental social motives, as mate seeking and mate retention, affiliation, and self-protection. However, less is known about the relation between tendency to tell jokes and more general styles of self-presentation, that is, tactical ways of behaving that can be used in many social interactions. In our study (N = 139 Polish men aged 18 to 60 [M = 29.94, SD = 11.66]), we wanted to examine the relationships between self-presentation styles (e.g., self-promotion and self-depreciation), humor styles (e.g., affiliative, self-enhancing, aggressive, and self-defeating), and tendency to tell jokes in adult men. We found that men focused on self-promotion produced humor more often and their humor styles contained more affiliative and self-enhancement aspects. Moreover, men's use of affiliative humor completely mediated the relationship between their self-promotion and their tendency to joke. We also found that men oriented on self-depreciation use more self-defeating humor, but their self-defeating motivation does not correlate with their tendency to joke. Our results suggest that men may tell jokes, especially those involving affiliative humor, to tactically achieve their self-promotion goals.